Establishment of an in vitro method for micropropagation of ironwort, (Sideritis raeseri Boiss. & Heldr.) - Valbona SOTA; Donald SHUKA; Shawky BEKHEET; Efigjeni KONGJIKA (Acta Agriculturae Slovenica, 2023)
Ironwort / Mountain Tea (Sideritis raeseri Boiss & Heldr.) is an endangered (EN) plant species in Albania. This study aimed to develop a rapid clonal propagation protocol using in vitro methodologies. The ironwort seeds were pre-treated with three concentrations of GA3 (250, 500, and 1000 mg l-1). During the inoculation stage, two types of culture media, Murashige & Skoog (MS) and Woody Plant Medium (WPM), were tested, and the effects of both GA3 concentration and culture media used were evaluated. For the subculture stage, three cytokinins (6-benzylaminopurine / BAP, kinetin, zeatin) at four concentrations (0.5; 1.0; 1.5; 2.0 mg l-1), were compared for the RGR index, while for the rooting stage, two different auxins (1-naphthaleneacetic acid / NAA and indole-3-butyric acid / IBA) at four concentrations (0.5; 1.0; 1.5; 2.0 mg l-1) were tested. GA3 at 500 mg l-1 and MS medium resulted as more effective. The highest value of the RGR index during the subculture stage was obtained in the MS nutrient medium supplemented with BAP at 1.5 mg l-1. For rhizogenesis response, IBA was more effective for roots and length number. Based on these results, in vitro methodologies can be a promising tool for the mass production of this endangered plant species and with possible applications for enhancing the production of valuable nutraceuticals.